2014
DOI: 10.1161/strokeaha.114.005115
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin Deficiency Impairs Stroke Recovery

Abstract: Background and Purpose Endoglin (ENG) deficiency causes hereditary hemorrhagic telangiectasia-1 (HHT1) and impairs myocardial repair. Pulmonary arteriovenous malformations (AVM) in HHT1 patients are associated with a high incidence of paradoxical embolism in the cerebral circulation and ischemic brain injury. We hypothesized that ENG deficiency impairs stroke recovery. Methods Eng heterozygous (Eng+/−) and wild-type (WT) mice underwent permanent distal middle cerebral artery occlusion (pMCAO). Pial collatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 28 publications
6
32
0
2
Order By: Relevance
“…4b & c ). These data confirm previous observations that the ability of Eng -deficient monocyte homing to angiogenic/injury tissue is impaired [17,29]. …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…4b & c ). These data confirm previous observations that the ability of Eng -deficient monocyte homing to angiogenic/injury tissue is impaired [17,29]. …”
Section: Resultssupporting
confidence: 92%
“…This is consistent with our previous finding that the homing and clearance of Eng -deficient macrophages in injury tissue (angiogenic region) are impaired [29]. The accumulation of macrophages in the angiogenic region of Eng -deficient mice could be due to persistent infiltration and delayed clearance of BM-derived macrophages.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, in an experimental model of brain arteriovenous malformations in mice induced by local injection of the VEGF gene, it has been reported that, compared with control mice, Eng-deleted mice show fewer macrophages homed to the angiogenic area 2 weeks after angiogenic stimulation [240]. This phenomenon can be explained by the reduced homing of monocytes in the injured tissue in Eng-deficient mice, as previously reported in other models [20,27,239]. However, Eng +/− animals showed more tissue macrophages at 8 weeks the stimulus, when arteriovenous malformations were already formed, resulting in persistent inflammation, which can be explained by an impaired clearance of Eng-deficient macrophages in the injured tissue (angiogenic region) [239,240].…”
Section: Endoglin Regulation Of Mural and Mononuclear Cell Recruitmentsupporting
confidence: 65%
“…In Eng +/− mice subjected to an experimental infarct, microvascularity within the infarct zone was strikingly lower than that in wild type mice, which resulted in a greater deterioration in cardiac function [20]. Moreover, after distal middle cerebral artery occlusion, Eng +/− mice showed larger infarct/atrophic volumes and fewer infiltrating macrophages than wild type animals, suggesting that endoglin deficiency impairs brain injury recovery by impairing macrophage homing, delaying inflammation resolution, and reducing angiogenesis [239]. Furthermore, in an experimental model of brain arteriovenous malformations in mice induced by local injection of the VEGF gene, it has been reported that, compared with control mice, Eng-deleted mice show fewer macrophages homed to the angiogenic area 2 weeks after angiogenic stimulation [240].…”
Section: Endoglin Regulation Of Mural and Mononuclear Cell Recruitmentmentioning
confidence: 99%